Nickel‐Catalyzed Asymmetric Reductive Diarylation of Vinylarenes. (11th February 2019) - Anthony, David; Lin, Qiao; Baudet, Judith; Diao, Tianning
Abstract: A nickel‐catalyzed asymmetric diarylation reaction of vinylarenes enables the preparation of chiral α, α, β‐triarylated ethane scaffolds, which exist in a number of biologically active molecules. The use of reducing conditions with aryl bromides as coupling partners obviates the need for stoichiometric organometallic reagents and tolerates a broad range of functional groups. The application of an N ‐oxyl radical as a ligand to a nickel catalyst represents a novel approach to facilitate nickel‐catalyzed cross‐coupling reactions.